2003
DOI: 10.1016/s1607-551x(09)70463-2
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyoma of the Urinary Bladder: A Case Report

Abstract: Leiomyoma of the urinary bladder is a rare tumor and constitutes 35% of benign mesenchymal bladder tumors. Herein, we report a case of leiomyoma of the bladder. A 32-year-old female was incidentally found to have an abnormal bladder mass on abdominal ultrasound during work-up for infertility. Bimanual examination then revealed a mass on the right side near the bladder neck area. On cystoscopic examination, an external compression mass covered with normal bladder mucosa could be seen at the right lateral wall. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
0
2
0
9
Order By: Relevance
“…Transurethral resection and fulguration are used in clinical practice as extremely minimally invasive treatment modality for small sized lesions which could be identified endoscopically. On the other hand, previous studies showed that repeating surgical interventions could be needed as secondary to incomplete resection in 18% of endovesical leiomyomas resected by transurethral method [20]. Especially for leiomyomas of intramural or extravesical nature which may have large sizes, open, laparoscopic or robotic mass enucleation and partial or total cystectomy are among the treatment modalities [4,20].…”
Section: Discussionmentioning
confidence: 99%
“…Transurethral resection and fulguration are used in clinical practice as extremely minimally invasive treatment modality for small sized lesions which could be identified endoscopically. On the other hand, previous studies showed that repeating surgical interventions could be needed as secondary to incomplete resection in 18% of endovesical leiomyomas resected by transurethral method [20]. Especially for leiomyomas of intramural or extravesical nature which may have large sizes, open, laparoscopic or robotic mass enucleation and partial or total cystectomy are among the treatment modalities [4,20].…”
Section: Discussionmentioning
confidence: 99%
“…Le léiomyome peut se développer en endovésical, intra-mural, ou dans un endroit extra vésical (bassinet, uretère et urètre) [8]. La localisation vésicale constitue la localisation la plus fréquente et représente 35% des tumeurs bénignes vésicales [2, 5, 7].…”
Section: Discussionunclassified
“…Pueden ser hallados en cualquier parte del tracto urinario, la mayoría se originan en la vejiga y corresponden al 1%-5% de los tumores de vejiga. [1][2][3][4] Se presentan con mayor frecuencia en la población femenina y deben ser considerados como diagnóstico diferencial en cualquier tumor de vejiga. 1 Son tumores que pueden ser asintomáticos a menos que afecten la función del tracto urinario inferior, generando síntomas urinarios obstructivos, irritativos y/o hematuria.…”
Section: Introductionunclassified
“…[1][2][3][4] Se presentan con mayor frecuencia en la población femenina y deben ser considerados como diagnóstico diferencial en cualquier tumor de vejiga. 1 Son tumores que pueden ser asintomáticos a menos que afecten la función del tracto urinario inferior, generando síntomas urinarios obstructivos, irritativos y/o hematuria. La forma más común de presentación son los endovesicales (86%), seguidos de extravesicales (30%) quienes tienden a ser asintomáticos y de diagnóstico incidental.…”
Section: Introductionunclassified
See 1 more Smart Citation